Cam Simulation and Dimensional Verification of CNC-Machined Orthopaedic Femoral Components: Toolpath Optimization and 3D-Scan Metrology - Setyoadi, Yuris; Rifky Ismail; Bayuseno, Athanasius Priharyoto; I Nyoman Jujur; Novriansyah, Robin; Darmanto; Prawibowo, Hartanto; Anggoro, Paulus Wisnu (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study investigates the optimization of manufacturing femoral components for Total Knee Replacement (TKR) using Computer-Aided Manufacturing (CAM) simulation and 5-axis CNC milling, followed by dimensional verification based on 3D scanning. The machining process was simulated in Autodesk PowerMill to generate collision-free toolpaths for AISI 316L stainless steel. Dimensional verification was conducted by comparing the 3D-scanned physical model (using Creality CR-Scan Ferret Pro) with the original CAD model in Geomagic Control X. The metrological analysis showed a Root Mean Square (RMS) deviation of 0.5317 mm and an average positive deviation of 0.2572 mm. Spatial deviation analysis revealed significant dimensional variations, with a maximum deviation of +2.5761 mm and a minimum deviation of -2.5713 mm. Specifically, in critical functional regions, the medial and lateral condyles exhibited deviations ranging from -0.4683 mm to 0.232 mm, while the patellar groove showed a deviation of 0.1989 mm. Although the machining strategy successfully produced the complex implant geometry, the tolerance distribution data indicated that only 17.22% of the surface fell within the strictly specified tolerances, highlighting the need for further optimization of cutting parameters and fixturing strategies to minimize surface roughness and dimensional inaccuracies.